New locality of Botrychium matricariifolium in south-eastern Poland – characteristics of the habitat and some plant traits - Wójcik, Tomasz; Ziaja, Maria (Ecological Questions, 2022)
Botrychium matricariifolium is a critically endangered species in Poland. In 2020, a new locality of this rare fern was found in the Góra Chełm forest reserve (Strzyżowskie Foothills). The population comprised 58 individuals. The fern was found in the Carpathian beech fertile complex Dentario glandulosae-Fagetum at a forest margin located near an unused quarry. The community comprised 29 vascular plant species. The dense layer of trees (90%) was composed of Acer pseudoplatanus, Abies alba, and Fagus sylvatica. The greatest coverage in the undergrowth was achieved by Dentaria glandulosa, Dentaria bulbifera, Galeobdolon luteum, and Mercurialis perennis. The mean height of the ferns was 14.9 cm. The trophophores had 3 branches each and were 1.1-3.4 cm long (mean: 2.1 cm). They had 5 to 9 pinnae. The length of the sporophore ranged from 2.3 to 8.3 cm (mean: 5.1 cm). It had from 12 to 183 sporangia (mean: 62). In 2021, the locality was re-verified, and 30 sporulating individuals were recorded. No factors threatening the species were noted. The population is in good condition and does not require any special active protection measures.